Results of using professional motor test in the program of physical rehabilitation of football players after injuries of the ankle joint - Шарбель, Юсеф; Підкопай, Тетяна; Підкопай, Денис (Slobozhanskyi Herald of Science and Sport, 2019)
Youssef Charbel, Tetiana Podkopai & Denis Podkopai Purpose: improving the results of physical rehabilitation of football players aged 18–24 with intra-articular injuries of the ankle joint at the outpatient stage by optimizing and increasing the effectiveness of the differentiated use of rehabilitation measures that were integrated into the training process. Material & Methods: this work was based on the results of observation of 36 athletes who play football in the clinic of the “MirMajidErslan” Medical Center in Beirut (Lebanon) based on the physical therapy room. Victims of the control group received a set of rehabilitation measures according to the traditional program of physical rehabilitation adopted in this clinic. The victims of the main group were offered a set of rehabilitation measures of the program developed by us, which included the use of therapeutic gymnastics integrated into the training process, the use of modified ethnic Arabic bath procedures and the consistent use of procedures with elements of ethnic Arabic massage. Results: analysis of the results of physical rehabilitation showed that with a positive dynamics of changes in the functional status of the victims of both clinical groups, more pronounced and significantly better results were obtained from the victims of the main group, who underwent physical rehabilitation according to our proposed program. Conclusions: the proposed program of physical rehabilitation of injured athletes after internal articular injuries of the ankle at the outpatient stage, which is included in the training process, is effective and can be recommended for general use.